STRATEGI MANAJEMEN PRODUKSI PROGRAM ACARA KHAZANAH DALAM MEMPERTAHANKAN EKSISTENSI PROGRAM DI TRANS 7 - Dian Filzah Aytis; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Khazanah Trans7 is one of the educative and informative programs that provide important and interesting information related to the Islamic world. Impressions containing excerpts and illustrations relating to the theme shown and accompanied by verses of al-quran and hadithThis research uses qualitative descriptive method, while the object of the research is the production of Khazanah Program 7 Trans and the subject of research includes employees who are members of the Khazanah production team. Data collection techniques used were interview, observation and also documentation.The results of this study show Khazanah apply 4 stages in the production management program, namely: First, Planning (Planning), including content planning, cost, means, and time. Second, Organizing (Organizing) For the entire team on duty placed in accordance with the expertise of each respectively. Third, Pengarahanyang conducted is to provide direction to the team in the production and post production. Fourth, Controlling The supervision is divided into three phases: supervision of material conducted before the coverage process, supervision at the time of production and supervision at the time of pre production. All series of processes is a form of production management process Khazanah program in maintaining the existence of the program.Keyword : Management Strategy, Production, Khazanah Program